Meningkatkan Keterampilan Menulis Teks Fiksi Dengan Menggunakan Model Cooperative Integrated Reading and Composition (CIRC) Pada Siswa Kelas Tinggi: Fictional Text Writing Skills, CIRC Learning Model, Elementary School - Yeni Puspa Dewi; Dyah Lyesmaya; Din Azwar Uswatun (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Abstract: Research through a Cooperative Integrated reading and Composition (CIRC) model aims to improve the writing skills of fictional text on high-class elementary school students. The type of research used is class action research (PTK). The number of students examined in this study was 29 people consisting of 14 male students and 15 female students. Data collection tools using tests and observation sheets. The results showed the value of writing skills of fictional text on the activity of pre-cycle percentage averages 49% with sufficient categories, in the I cycle the average percentage of 64% with good categories, while on the cycle II average percentage of 76% with Good category increased from cycle I to cycle II with a value of 71% has reached the value of the KKM (70). While on the teacher activity cycle I obtained a value of 62 with a good category, cycle II gained a value of 82 with a good category increase from cycle I to cycle II with a value of 81% has reached the value of the KKM (70) and the student activity cycle I gained a value Averaging 56 with sufficient categories, cycle II gained a value of 73 with a good category of such increase with a value of 72% increase in cycle I to cycle II has reached KKM (70). This study can prove that implementing a learning CIRC can improve fiction text writing Skills in class IV in Brawijaya Sukabumi Elementary School 2018/2019.